Saxitoxin in Alaskan commercial crab species - Patricia A. Tester; Bruce Wright; Richard Wayne Litaker; Patryce McKinney; William C. Holland; Steven R. Kibler; Mark W. Vandersea (PLoS ONE, 2025)
Paralytic shellfish poisoning (PSP) is a pervasive human health concern associated with subsistence, recreationally and commercially harvested Alaskan shellfish. PSP is caused by saxitoxins (STX), a family of structurally similar neurotoxins produced by the marine microalgae Alexandrium catenella (formerly A. fundyense). These toxins accumulate in filter-feeding shellfish such as clams, mussels and oysters. While PSP is commonly associated with consuming bivalves, toxic STX levels can also be found in crab viscera (crab butter). The first cases of PSP from consuming Dungeness crab viscera (Metacarcinus magister) were reported in 1992. Although this incident and others did not involve commercially harvested crab, they did impact management of the Dungeness crab fishery in Alaska. Current regulations in southeast Alaska permit the sale of whole Dungeness crab, whereas those in the Kodiak Archipelago must have their viscera removed post-harvest to prevent PSP. This study examines the impacts of STXs and current regulations on the Alaskan crab fishery, with a focus on Dungeness crab. Data on commercial landings and the value of harvested Dungeness crab and processed products showed that regulations to protect human health, combined with market forces over the past 30 years, have shifted the fishery’s focus toward Dungeness crab products without viscera. The study also presents time series data on STX concentrations in Dungeness crab from 1992 to 2023, along with maps indicating collection locations and their associated toxicity levels. The same data for King crab (Paralithodes or Lithodes spp.) and Tanner (Snow) crab (Chionoecetes spp.) are included to assess the prevalence of STX in these commercially harvested species. Further, a preliminary analysis suggests regional variations in the toxicity of A. catenella strains could affect regional shellfish toxicity.